Dimensionality and Reliability of the Intentions to Seeking Counseling Inventory with International Students - Yee, Terence; Rachel P Smith, (Journal of International Students, 2021)
To date, the Intentions to Seek Counseling Inventory (ISCI) is the most widely used instrument to measure psychological help-seeking intentions. However, the ISCI is yet to be validated with international students. In this study, we examine the dimensionality and reliability of the ISCI by performing exploratory factor analysis, Cronbach alpha reliability analysis, and split-half reliability analysis in a sample of international students (N = 183). We find a two-factor, 15-item assessment that explains 49.92% of the common variance. Our findings provide support for the use of ISCI with international students, albeit with different dimensionality. Implications of the findings for both research and practice are discussed.